Ericoid mycorrhizal fungus enhances microcutting rooting of Rhododendron fortunei and subsequent growth. (1st September 2020) - Wei, Xiangying; Chen, Jianjun; Zhang, Chunying; Liu, Hong; Zheng, Xiuxia; Mu, Jingli
Abstract: Adventitious root (AR) formation is a unique feature of plant reproduction and plays a vital role in crop production as many horticultural and forestry plants are propagated through cuttings. A growing number of reports have shown that microbes, particularly mycorrhizal fungi are able to promote AR formation, but the underlying mechanisms remain largely unclear. This study established an in vitro culture system and investigated AR formation in microcuttings of Rhododendron fortunei Lindl. inoculated with Oidiodendron maius Barron Om19, an ericoid mycorrhizal fungus strain. Hormones and precursors involved in the biosynthesis of indole-3-acetic acid (IAA) in Om19 mycelium were analyzed. Om19 was able to produce a large quantity of tryptophan (Trp) and also indole-3-pyruvate (IPA) and IAA, indicating that IAA biosynthesis in Om19 could be through a Trp-dependent pathway. After inoculation of Om19, ARs were quickly formed in microcuttings. Symbiosis related genes were activated in ARs, and Om19 effectively colonized the roots. YUC3, a key gene in plant biosynthesis of IAA and genes involved in nitrogen (N) uptake and metabolism, phosphorus (P) uptake were highly upregulated. Plants absorbed significantly greater quantity of mineral nutrients, and their growth was substantially enhanced compared to the control plants without Om19 inoculation. A working model for Om19 enhanced AR formation was proposed. The rapid formation of ARs in cuttings could be due in part to the induction of IAA biosynthesized by Om19 and also attributed to Trp catalyzed biosynthesis of IAA in plants. AR formation, in turn, provided Om19 preferred sites for colonization. Our study suggested that in addition to promoting AR formation, Om19 could potentially be used as a new biofertilizer for enhancing production of ericaceous plants, such as blueberry, cranberry, and rhododendron.